2007
DOI: 10.1093/ajcn/85.4.1112
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of plant foods to the vitamin A supply of lactating women in Vietnam: a randomized controlled trial

Abstract: Background: More information is needed on the efficacy of carotenoids from plant foods in improving vitamin A status. Objective: We aimed to quantify the efficacy of provitamin A-rich vegetables and fruit in improving vitamin A status. Design: Breastfeeding women in 9 rural communes in Vietnam were randomly allocated to 1 of 4 groups: the vegetable group (n ҃ 73), which ingested 5.6 mg ␤-carotene/d from green leafy vegetables; the fruit group (n ҃ 69), which ingested 4.8 mg ␤-carotene/d from orange or yellow f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 19 publications
4
59
0
1
Order By: Relevance
“…26 Vitamin C was determined in 250 lL plasma by reversed phase chromatography using fluorescence detection. 27 Case-control sets were assayed in the same batch to minimize batch-to-batch variations.…”
Section: Laboratory Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…26 Vitamin C was determined in 250 lL plasma by reversed phase chromatography using fluorescence detection. 27 Case-control sets were assayed in the same batch to minimize batch-to-batch variations.…”
Section: Laboratory Analysismentioning
confidence: 99%
“…BMI was selected instead of waist circumference, because BMI had no missing values. Participants were cross-classified according to quartiles of intake of vitamins and carotenoids and categories of smoking status (current, former and never smokers), alcohol consumption [low (0-3 g/day for women and 0-6 g/day for men), moderate (3-12 g/ day for women and 6-24 g/day for men) and high (>12 g/ day for women and >24 g/day for men)], BMI (<25, [25][26][27][28][29][30] and >30 kg/m 2 ) and physical activity (inactive, moderately inactive, moderately active, active participants). Deviation from multiplicative interaction was tested by likelihood ratio tests comparing models including multiplicative interaction terms with models without interaction terms.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Vitamin A retinol activity equivalents (RAE) were used, where the retinol equivalency is assumed to be 12:1 for b-carotene and 24:1 for a-carotene and bcryptoxanthin (17) . However, it has been suggested that the retinol equivalency of provitamin A carotenoids from green and yellow vegetables is as high as 26-28:1, while from fruits it is 12:1 (18)(19)(20) . We thus calculated 'alternative vitamin A RAE' intake data assuming that provitamin A from green and yellow vegetables had a retinol equivalency of 26:1 and that from fruits, orange vegetables and orange and yellow roots had a retinol equivalency of 12:1.…”
Section: H Dietary Recallmentioning
confidence: 99%
“…Jagung provit-A mengandung vitamin A (betakaroten) 8-15 μg/g, lebih tinggi dibanding jagung biasa yang hanya mengandung betakaroten 1,0 μg/g. Betakaroten dapat mencegah defisiensi vitamin A, meningkatkan daya tahan tubuh, membantu pertumbuhan gigi, mencegah buta dini, dan meningkatkan nafsu makan (Science Daily, 2008;Nutra, 2008;Cong Khan et al, 2007;Bwibo dan Neumann, 2003).…”
Section: Pendahuluanunclassified